THE RESILIENCE OF THE BANKING SYSTEM OF THE REPUBLIC OF MOLDOVA DURING CRISIS PERIODS: EVIDENCE FROM THE LAST 10 YEARS - Ion VEVERIȚĂ; Ion PÂRȚACHI (Eastern European Journal of Regional Studies, 2025)
As a developing country with an open economy, the Republic of Moldova is highly dependent on the import of energy resources and sensitive to the exchange rates fluctuations, the resilience of the banking system is crucial for maintaining and development of the financial intermediation (deposits taking and loans providing). This is because reliable and stable intermediation services are provided for clients from one side and help to implement the investment programs that are supported by international financial organizations and the local government from the other side. As a robust economy requires a comprehensive and coherent legal environment, authorities implemented regulatory frameworks that build more stability and predictability and diminish the potential negative impact of crises that can affect the financial system and as a result of client trust in the robustness of banks. Quantitative analysis performed on freely available data sources stated the resultative effect on shocks impact, but did not take into consideration the corrective impact of the actions that the government activated during the extreme economic condition environment. Although the direct limitation of the profit distribution from the supervisory authority is not appreciated by the market players and their shareholders, there are reasons that preserve resilience at a controlled and sustainable level, the attractivity of the banking sector for investors on increasing/maintaining the investments or entering the market remains valid. As a next step, development of a high-frequency early warning indicator enhances the ability to detect operational disturbances within the banking system.